Perancangan Aplikasi Sistem Pendukung Pelayanan Kepuasan Pelanggan Kepuasan Pelanggan Restoran Berbasis Web (Studi Kasus Baso Aci Neng Anya) - Hadi Ramadhan; Atang Susila (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Baso aci neng anya is a franchise business engaged in the culinary field in the form of a fast food restaurant or fast food which is located at Jalan Situ Babakan Pochis III No. 30, Pamulang, Tangerang City. So far, there is no questionnaire to find out customer satisfaction, so every complaint is submitted orally. The problem is that when complaints are conveyed orally to Baso Aci Neng Anya employees, often the employee who receives the complaint forgets to convey it to management because the complaint is not written down and not documented. Based on the existing problems, a Design and Development of a Customer Satisfaction Service Support System Application was made at Baso aci Neng Anya Pamulang Branch using the WEB-Based PHP method, so that it can help to determine the level of customer satisfaction. This application is web-based because it makes it easier to implement and can also be accessed on all platforms that can use a web browser. Based on the results of the application trial for 30 respondents with an average result in quadrant I, namely the main achievement and quadrant II, namely maintaining the achievement of quadrant III, low priority quadrant IV, very satisfied, besides that the application can display the results of customer satisfaction analysis recommendations in the form of a report in the form of a Satisfaction Review Website Customers for the owner of Baso Aci Neng Anya so which service factors must be improved and improved customer satisfaction analysis recommendations in the form of a report in the form of a Satisfaction Review Website Customers for the owner of Baso Aci Neng Anya so which service factors must be improved and improved.